Public survey data of the research study “Ready for change? Sustainable management of common natural resources”: Thematic survey of 2021 - University of Latvia, Advanced Social and Political Research Institute (ASPRI) of the Faculty of Social Sciences (My University, 2023)
The data set (see the description of the data set below) and its accompanying information include sociological survey conducted in March 2021 titled "Citizens' attitudes to biodiversity" as part of the Fundamental and Applied Research project "Ready for change? “Sustainable management of common natural resources” (lzp-2019/1-0319). Ongoing environmental collapse is putting increasing pressure on ecosystems and social communities, particularly, in the regions of Latvia. Survey has been conducted to reveal attitudes, understanding, and practices of biodiversity, particularly in forest ecosystems. The survey achieved a sample size of 410 respondents – Latvia internet users population aged 18 and older. The anonymized dataset was obtained by conducting an internet survey (CAWI) within the SKDS internet survey panel. Data collection took place in March 25th, 2021. The survey was conducted by the research center SKDS, commissioned by researchers from the University of Latvia within the framework of the Fundamental and Applied Research project "Ready for change? Sustainable management of common natural resources” (lzp-2019/1-0319), conducted at the Advanced Social and Political Research Institute (ASPRI) of the Faculty of Social Sciences of the University of Latvia (LU). The research was funded by the Latvian Council of Science. Description of the data sets: 1. Survey data files and variable information in Latvian and in English (Files: RfC_Dati_2021_biod_forests.csv and RfC_Dati_2021_biod_forests_EN.sav in English, RfC_Dati_2021_biod_forests_LV.sav – in Latvian); 2. Variable and Value Labels for Data File in Latvian and in English (Files: RfC_VarInfo_2021_biod_forests.xlsx). The datasets include 57 variables, of which: 1. 54 variables are related to survey questionnaire questions and responses, including combinations of socio-demographic variables. (Survey questionnaire in Latvian: RfC_Aptaujas_anketa_2021_biod_forests_LV.docx and in English: RfC_Aptaujas_anketa_2021_biod_forests_EN.docx); 2. Additionally, there are 3 variables - ID variable (ID), interview length, in seconds (Time), the combined variable for status of forest ownership (in ownership or in use) (mip) – own forest (response code 1) and do not own forest (response code 0), which is a consolidated question Q6R5 in the survey questionnaire (Q6R5A1, Q6R5A2, Q6R5A3, Q6R5A4).
Keywords: environmental attitude; attitude towards biodiversity; forest resources; support for solutions of reducing biodiversity loss; Research Subject Categories::SOCIAL SCIENCES::Social sciences